Pengaruh overconfidence, risk tolerance, return, financial literacy, financial technology terhadap keputusan investasi - Mahardhika, Muhammad Danang; Asandimitra, Nadia (Jurnal Ilmu Manajemen, 2023)
This research examines investment decisions among students in Surabaya City and analyses the relationship between Overconfidence, Risk Tolerance, Return, Financial Literacy, and Financial Technology on investment decisions. The research subjects are students in Surabaya City, and data collection is done using a purposive sampling technique. A total of 210 respondents were obtained by distributing online questionnaires. This research is causal-conclusive, and the Structural Equation Modeling (SEM) analysis technique is employed using AMOS software version 24. The results of this study indicate that Risk Tolerance, Return, Financial Literacy, and Financial Technology have a significant positive influence on investment decisions, while Overconfidence does not have an impact on investment decisions. This study can be a valuable reference for various parties, especially investors, emphasising the importance of making informed and rational decisions when investing in the capital market. Therefore, students in Surabaya must have the ability to accept risks when making investments so that investment decisions will be higher. Profit is something that is coveted by investors. Therefore a high return will increase investment decisions because it will provide high profits. Students in Surabaya, as potential investors, must have good financial literacy so that investment decisions will be higher. Knowledge of financial technology in this globalisation era will significantly influence investment decisions.